DIFFERENT FORMS OF CORAL FUNGIA PAUMOTENSIS, IN EACH DIFFERENT LOCATION ON THE ISLAND OF MAMBURIT, SUMENEP DISTRICT - sawiya sawiya; Abdul Muqsith (Universitas Tidar, 2022)
Coral morphological characters are mainly caused by environmental factors. The method used is random sampling with one sample, two repetitions at each station. The stations selected were Leeward I, Leeward II, Windward I, and Windward II. Based on the results obtained in the waters of Mamburit, Fungia paumotensis, General physical characteristics included a hilly colony surface, pointed teeth and small grains and curved corals. Morphological characters show differences from discrete and morphometric characters in each sample where these differences are influenced by the environment